2020
DOI: 10.1177/0194599820926464
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction: A Highly Prevalent Symptom of COVID‐19 With Public Health Significance

Abstract: Objective Coronavirus disease 2019 (COVID-19) is a global pandemic affecting millions of individuals, killing hundreds of thousands. Although typically described with characteristic symptoms of fever, cough, and shortness of breath, greater understanding of COVID-19 has revealed myriad clinical manifestations. Olfactory dysfunction (OD)—hyposmia and anosmia—has recently been recognized as an important symptom of COVID-19 and increasingly gained traction as a public he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
110
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 13 publications
11
110
1
10
Order By: Relevance
“…6,28,29 OD in the setting of COVID-19 is also highly correlated with decreased sense of taste. 6,28,29 Participants from this cohort have been previously studied with respect to the prevalence, timing, and severity of sinonasal symptoms as well as classic COVID-19 symptoms of fever, cough, and shortness of breath. 19 The prevalence of OD was comparable to past studies, and we also found that OD was quite severe when it occurred.…”
Section: Covid-19 Remains a Global Threat To Public Health Having Afmentioning
confidence: 96%
See 1 more Smart Citation
“…6,28,29 OD in the setting of COVID-19 is also highly correlated with decreased sense of taste. 6,28,29 Participants from this cohort have been previously studied with respect to the prevalence, timing, and severity of sinonasal symptoms as well as classic COVID-19 symptoms of fever, cough, and shortness of breath. 19 The prevalence of OD was comparable to past studies, and we also found that OD was quite severe when it occurred.…”
Section: Covid-19 Remains a Global Threat To Public Health Having Afmentioning
confidence: 96%
“…[1][2][3] COVID-19 has classically been described by symptoms of fever, cough, and shortness of breath as well as constitutional symptoms such as fatigue and myalgias, 2,4,5 although more recent studies have described a myriad of other COVID-19 clinical manifestations including chemosensory dysfunction, ie, decreased sense of smell and taste. 6 With a mortality rate that is widely publicized and understood in the lay public to be an order of magnitude greater than influenza, COVID-19 may be a significant source of emotional strain on the affected individual. Previous studies of endangering diseases, such as cancer, diabetes, or heart disease, have found that affected patients experience much higher rates of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of systematic reviews [6][7][8][9][10][11][12] have been published already, during the early stages of the pandemic in Europe and USA. However, in light of continuous scientific updating, we believe that our study can provide a more holistic approach to current knowledge of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Chemosensory symptoms may present as viral prodromes or be concomitant with the development of other disease symptoms. 12 Although olfactory dysfunction can be seen with rhinoviruses, parainfluenza, Epstein-Barr virus, and other coronaviruses, this symptom is typically linked with rhinorrhea and nasal obstruction, whereas there is accumulating evidence that SARS-CoV-2 associated olfactory dysfunction is seen independent of nasal congestion. 2,6 Anosmia in the absence of other symptoms is reported in as many as 1 of 6 individuals with SARS-CoV-2 infection.…”
mentioning
confidence: 99%